Montmorillonite K10 Clay Catalyzed Synthesis of 4-Aryltetrahydropyrans: A One-Pot, Multicomponent, Environmentally Friendly Prins–Friedel–Crafts-Type Reaction - Dintzner, Matthew R. (Synlett, 2013)
The Montmorillonite K10 clay catalyzed synthesis of 4-aryltetrahydropyrans is presented as a one-pot, multicomponent, environmentally friendly Prins–Friedel–Crafts-type reaction.
Keywords: aldehydes; cyclization; green chemistry; heterogeneous catalysis; multicomponent reaction